Assessment of the Therapeutic Value of the Innovative Multicomponent Antitumor Drugs - Archil Chirakadze; Lia Chelidze; Nodar Mitagvaria; Nelly Makhviladze; Tengiz Chubinishvili; Giorgi Palavandishvili; Khatuna Tserodze; Zakaria Buachidze (Research Retrieval and Academic Letters, 2025)
The most modern and advanced method of treating cancerous tumors is undoubtedly the charged particle therapy which should be mostly concentrated in the tumor area due to the maximum dissipation of the energy of charged particles in the region of the Bragg peak. The real spread of hadron therapy is much slower than expected, most likely due to its extremely high cost, research intensity and requirements to medical and engineering staff. All this results in unacceptably long delays in registration and implementation of new innovative drugs, and in turn, results in the suffering and death of tens of thousands of patients. In addition, the financial risks and difficulty of obtaining funding for the most pioneering and innovative research increases dramatically. Therefore, a significant increase in the biological effectiveness and safety of proton therapy is an acute and urgent need of the current day to provide the rapid and sustainable development of proton and heavy ion therapy. The reported study deals with the development of innovative multicomponent synergistic anticancer combinations containing the FDA and testing of their specific selectivity to cancer cells and acute toxicity to chick embryos.